2008
DOI: 10.1007/s11433-008-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior of Zr-based bulk metallic glass and composite in the supercooled liquid region

Abstract: A Zr-based bulk metallic glass (BMG) with a composition of (Zr 75 Cu 25 ) 78.5 Ta 4 Ni 10 Al 7.5 and a bulk metallic glass matrix composite (BMGC) with a composition of (Zr 75 Cu 25 ) 74.5 Ta 8 Ni 10 Al 7.5 have been prepared by copper-mold casting. The compressive deformation behavior of the BMG and BMGC was investigated in the supercooled region at different temperatures and various strain rates ranging from 8×10 −4 s −1 to 8×10 −2 s −1 . It was found that both the strain rate and test temperature significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…But STZs of the samples annealed for 8 min takes more atoms into action, indicating that STZs of the more ordered structures involve more atoms. Chen et al also found that the V act for the (Zr 75 Cu 25 ) 74.5 Ta 8 Ni 10 Al 7.5 BMGCs is much higher than that of the corresponding BMGs [22]. On the contrary, Fu et al [8] have presented that V act is reasonably constant with composition for Zr-Cu-Al BMGCs with various volume fractions of particles.…”
Section: Viscosity Flow Behavior Of All the Bmgcsmentioning
confidence: 98%
“…But STZs of the samples annealed for 8 min takes more atoms into action, indicating that STZs of the more ordered structures involve more atoms. Chen et al also found that the V act for the (Zr 75 Cu 25 ) 74.5 Ta 8 Ni 10 Al 7.5 BMGCs is much higher than that of the corresponding BMGs [22]. On the contrary, Fu et al [8] have presented that V act is reasonably constant with composition for Zr-Cu-Al BMGCs with various volume fractions of particles.…”
Section: Viscosity Flow Behavior Of All the Bmgcsmentioning
confidence: 98%
“…With an increase in temperature to the supercooled liquid region, which is defined by the temperature range between the glass transition temperature T g and the crystallization temperature T x , the amorphous alloy exhibits homogeneous deformation and viscous flow [13][14][15][16]. Consequently, the amorphous powders are always consolidated in the supercooled liquid region using their viscous flow characteristics by a conventional consolidation method such as vacuum hot pressing [17] and spark plasma sintering (SPS) [18].…”
mentioning
confidence: 99%